Investigation of Schools, Students, Teachers and Classrooms Statistics in Special Education Institutions in the Last 20 Years in Turkey - Dinçer, Nevzat; Şahin, Süleyman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The most important aim of the education system is; to help solve the possible problems of all children in their developmental processes and to provide them with educational services in the areas they need. The purpose of special education in this system is; To provide equal opportunities in education to individuals who cannot benefit from normal education processes for any reason. In order to achieve this, it is important to define individuals in need of special education, to establish and supervise special education institutions, to prepare special education programs according to the developmental characteristics and individual competencies of individuals in need of special education, and to adapt existing programs. Aim: The aim of this research is to analyze the School, Student, Teacher and Classroom Statistics in Private Education Institutions in Turkey in the Last 20 Years and to make an assessment about the current situation. Methods: The Statistics of Schools, Students, Teachers and Classrooms in Private Education Institutions published by the Ministry of National Education of the Republic of Turkey between 2001-2020 were examined. Statistics have been obtained from the official website of the Ministry of National Education of the Republic of Turkey. Results: According to the research data, while the number of private education institutions was 342 in the 2001-2002 academic year, this number increased by approximately 4 times to 1,417 in the 2019-2020 academic year. While the number of teachers in the 2001-2002 academic year was 2,834, this number increased by 5 times and reached 15,321 in the 2019-2020 academic year. While the number of students studying in 2001-2002 was 53,306, this number increased by 8 times in the 2019-2020 academic year and reached 425,774. When the students who receive formal education in special education institutions are compared with those in special education schools, special education classes and inclusive education, the majority of the students who receive education in total are educated in inclusive education. Conclusion: As the academic year progresses in Turkey, there is a certain increase in the number of schools, the number of students studying, and the number of teachers providing education in Private Education Institutions. In this context, it is thought that teaching the disabled education as a compulsory course in all education faculties and giving disabled education seminars in all schools will have positive effects for special education students.